Cystic dilatation of both extrahepatic bile ducts in a patient with primary sclerosing cholangitis - Erkan PARLAK; Meral AKDOĞAN; Nurgül ŞAŞMAZ; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-